Production and Storage Properties of Spray-Dried Red Beet Extract Using Polysaccharide-Based Carrier Systems - Zuanon, Larissa A. C. [UNESP]; Fuzari, Nathália C. [UNESP]; Ferreira, Sungil [UNESP]; Freitas, Mírian L. F. [UNESP]; Moser, Poliana [UNESP]; Nicoletti, Vânia R. [UNESP] (De Gruyter, 2019)
This study aimed to produce betalain-rich powders by spray drying red beet extract using modified starch and maltodextrin blends as carrier materials, as well as to investigate the product storage stability as affected by water sorption and light exposure. The influence of spray drying conditions and carrier blends on the process yield, water content and solubility of the powders, betalain retention, and color parameters was assessed using a central composite design 24. The results of this screening allowed selection of four samples to further evaluation concerning their morphological characteristics, particle size distribution, water sorption properties, and betalain stability under light exposure. Samples formulated with carrier blends composed of equal amounts of modified starch and maltodextrin, used in a concentration of 35g carriers/110g of initial solution resulted in the higher betalain stability during 98 days of storage under exposure to light. Even though this formulation showed similar water sorption behavior to the other formulations studied, it also showed the best mechanical properties, indicating lower susceptibility to powder collapse.
Keywords: betalains; light stability; maltodextrin; microencapsulation; modified starch